Exploring a Novel Tool to Measure Wandering Behavior in the Early Childhood Classroom. (April 2022) - Wallisch, Anna; Irvin, Dwight; Kearns, William D.; Luo, Ying; Boyd, Brian; Rous, Beth
Wandering, or random movement, affects cognitive and social skills. However, we lack methods to objectively measure wandering behavior. The purpose of this pilot study was to explore the use of the Ubisense real-time location system (RTLS) in an early childhood setting to explore wandering in typically developing (TD) children ( n = 2) and children with or at risk for developmental disabilities (WA-DD; n = 3). We used the Ubisense RTLS, a tool for capturing locations of individuals in indoor environments, and Fractal Dimension (FD) to measure the degree of wandering or the straightness of a path. Results of this descriptive, observational study indicated the Ubisense RTLS collected 46, 229 1-s location estimates across the five children, and TD children had lower FD ( M = 1.36) than children WA-DD ( M = 1.42). Children WA-DD have more nonlinear paths than TD children. Implications for measuring wandering are discussed.